2013
DOI: 10.2478/s11686-013-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of juvenile golden grey mullet Liza aurata Risso, 1810 in Sarıkum Lagoon Lake at Sinop, Turkey

Abstract: Juvenile golden grey mullet, Liza aurata were collected from Sarıkum Lagoon Lake which connected to the Black Sea at Sinop, Turkey and examined for parasitic fauna. A total of 219 fish were investigated throughout a 1-year period. Parasite species recovered were Trichodina lepsii, T. puytoraci, Gyrodactylus sp., Ligophorus cephali, Ligophorus mediterraneus, Solostamenides mugilis, Ascocotyle sp. (metacercaria) and Ergasilus lizae. Overall infection prevalence (%) and mean intensity values were 95.9% and 412.65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(16 reference statements)
2
2
0
Order By: Relevance
“…Moreover, T. heterodentata was found on endemic Aphanius danfordii for the first time, while the finding of other species recovered in the present study confirmed some previously reported trichodinid species and their host ranges. Trichodina acuta on Cyprinus carpio, T. macrosoma on Aphanius danfordii, T. lepsii and T. puytoraci on both Mugil cephalus and Liza aurata, and T. tenuidens on Gasterosteus aculeatus showed strict host specificity to only one host species or genus, while T. heterodentata and T. domerguei exhibited a wide host range, as has been previously reported by several authors (Özer, 2000, 2003aÖzer and Öztürk, 2004;Dove and O'Donoghue, 2005;Öztürk andÖzer, 2007, 2008;Martins et al, 2010;Öztürk, 2013;Öztürk and Çam, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, T. heterodentata was found on endemic Aphanius danfordii for the first time, while the finding of other species recovered in the present study confirmed some previously reported trichodinid species and their host ranges. Trichodina acuta on Cyprinus carpio, T. macrosoma on Aphanius danfordii, T. lepsii and T. puytoraci on both Mugil cephalus and Liza aurata, and T. tenuidens on Gasterosteus aculeatus showed strict host specificity to only one host species or genus, while T. heterodentata and T. domerguei exhibited a wide host range, as has been previously reported by several authors (Özer, 2000, 2003aÖzer and Öztürk, 2004;Dove and O'Donoghue, 2005;Öztürk andÖzer, 2007, 2008;Martins et al, 2010;Öztürk, 2013;Öztürk and Çam, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…cephalus, L. haematochielus, L. aurata, L. ramada, C. labrosus andL. saliens (ElHafidi et al, 1998, Ragias et al, 2005;Öztürk, 2013). In this study, prevalence values for this parasite were 14.6% on M. cephalus and 8.7% on L. aurata and our results agree with those reported by the above mentioned authors.…”
Section: Microcotylidae and Diplozoidae Speciessupporting
confidence: 92%
“…Pre-granulomas and granulomas associated with metacercariae were detected in all examined organs, with a higher prevalence in the kidney and heart. TM have a wide range of tissue distribution, as they have been reported in almost every organ of mugilids [ 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%